2021
DOI: 10.1126/scitranslmed.abb3107
|View full text |Cite
|
Sign up to set email alerts
|

A biliary immune landscape map of primary sclerosing cholangitis reveals a dominant network of neutrophils and tissue-resident T cells

Abstract: The human biliary system, a mucosal barrier tissue connecting the liver and intestine, is an organ often affected by serious inflammatory and malignant diseases. Although these diseases are linked to immunological processes, the biliary system represents an unexplored immunological niche. By combining endoscopy-guided sampling of the biliary tree with a high-dimensional analysis approach, comprehensive mapping of the human biliary immunological landscape in patients with primary sclerosing cholangitis (PSC), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 74 publications
4
58
0
Order By: Relevance
“…There were also a number of distinct pathways enriched only in PSC, including IL-17 and IL-22 pathways. It has recently been shown that biliary T cells from individuals with PSC display a CD103 + CD69 + effector memory phenotype that secretes both IL-17 and IL-22 [ 57 ]. Taken together, the authors' findings suggest that epigenetic modifications may be partly driving the altered immune landscape in PSC and PBC and could be potential targets for these orphan diseases, particularly PSC, for which there is currently no effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There were also a number of distinct pathways enriched only in PSC, including IL-17 and IL-22 pathways. It has recently been shown that biliary T cells from individuals with PSC display a CD103 + CD69 + effector memory phenotype that secretes both IL-17 and IL-22 [ 57 ]. Taken together, the authors' findings suggest that epigenetic modifications may be partly driving the altered immune landscape in PSC and PBC and could be potential targets for these orphan diseases, particularly PSC, for which there is currently no effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, neutrophils can directly interact with cholangiocytes via integrin β1 and elicit cholestasis ( 113 ). Neutrophils were also indicated as central immune cells in the pathogenesis of immune-mediated cholangiopathies such as primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC) ( 114 ). Recently their contribution to tissue repair was also discovered.…”
Section: Crosstalk Between the Immune System And Biliary Repairmentioning
confidence: 99%
“…It is evident from studies performed in a non‐IBD context that neutrophils and T cells crosstalk [ 16 ], and their conversation is not one of the lonesome kind: stromal cells in the microenvironment respond to T‐cell‐derived IL‐17 with induction of factors such as IL‐8, G‐CSF or GM‐CSF, crucial for neutrophil recruitment and survival [ 17 , 18 , 19 , 20 ]. Except for Th17 cells that are effector CD4 + T cells named after their ability to produce of IL‐17, also other types of T cells, such as γδT cells, mucosal associated invariant T cells, CD1d‐restricted NKT cells and subsets of CD8 + T cells, are able to produce IL‐17 [ 21 ]. Although neutrophils cannot directly respond to IL‐17 due to the lack of its receptor, Th17 cells can directly interact with human neutrophils through IL‐17‐independent mechanisms via production of GM‐CSF, TNF and IFN‐γ [ 22 ].…”
Section: Intimate Crosstalk Between Neutrophils and T Cells In Ibdmentioning
confidence: 99%